2023
DOI: 10.3389/fonc.2022.1094136
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second primary cancer among breast cancer patients: A systematic review and meta-analysis

Abstract: ObjectivesThe aim of this study was to estimate the extra risk of second primary cancer among breast cancer patients.Methods and materialsThis is a systematic review. A comprehensive search of literature was performed in PubMed, Web of Science, Cochrane library, and Scopus. The search included all published studies up to October 2022. This systematic review included studies published in the English language that reported the risk of second primary non-breast cancer [i.e., standardized incidence ratio (SIR)] am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…While our study did not assess cancer predisposition gene (CPG) status, the observed associations between first and second primary cancers suggest a potential role for CPG in contributing to the observed patterns. Ovarian cancer emerged as the most likely MPC among those with first primary breast cancer, supported by numerous studies and the established genetic link, especially in BRCA1/2 mutation carriers [32,33]. In line with other research, KCCH data revealed an increased risk of subsequent breast cancer after thyroid cancer.…”
Section: Discussionsupporting
confidence: 63%
“…While our study did not assess cancer predisposition gene (CPG) status, the observed associations between first and second primary cancers suggest a potential role for CPG in contributing to the observed patterns. Ovarian cancer emerged as the most likely MPC among those with first primary breast cancer, supported by numerous studies and the established genetic link, especially in BRCA1/2 mutation carriers [32,33]. In line with other research, KCCH data revealed an increased risk of subsequent breast cancer after thyroid cancer.…”
Section: Discussionsupporting
confidence: 63%
“…With the increasing attention to the development of comprehensive treatment for breast cancer, the death toll of patients has declined in recent decades [ 16 ]. However, breast cancer is still the largest cancer afflicting women worldwide, with a negative situation [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest that following a breast cancer (BC) diagnosis among survivors at 5, 10, and 15 years, there is a 3.6%, 8.2% and 13.9% chance of acquiring another neoplasm, respectively [3].…”
Section: Introductionmentioning
confidence: 99%